La crítica al objetivismo y la propuesta epistemológico-política contenida en el Cuaderno 11 (en español) - Balsa, Javier (International Gramsci Journal, 2023)
This article analyses the relationship between objectivity, science and political practice based on a rereading of especially Notebook 11 of Antonio Gramsci’s Prison Notebooks. In the first place, we put forward a reconstruction of his critique of science, objectivism and vulgar materialism. Secondly, we examine his proposal for a new synthesis, based on his work on common sense, and the type of organic intellectuals necessary for the development of this ideological work. Thirdly, we study the articulation that Gramsci establishes between determinism and the passivity of the subalterns. Last, we consider the way in which Gramsci recognizes the existence of a tension between ideology and science, between objectivity and subjectivity, and how, in his view, this self-same tension has its repercussions on the practice of ideological struggle.